The differential effects of ESG pillars on firm performance: Evidence from Asian banks - Dewiyanti, Silvia; Ismail, Tubagus; Uzliawati, Lia; Yazid, Helmi (Edelweiss Applied Science and Technology, 2026)
This study aims to examine the differential effects of Environmental, Social, and Governance (ESG) pillars on bank performance in Asia, where the integration of sustainability principles is still evolving. The analysis is based on data from 55 listed banks across eight Asian countries covering the period 2019–2023. Firm performance is measured using return on assets (ROA) and return on equity (ROE). A fixed-effects regression model with robust standard errors is employed to assess the relationship between each ESG pillar and financial performance. The results reveal that governance practices significantly enhance bank performance, emphasizing the importance of board accountability, transparency, and shareholder protection. In contrast, environmental and social dimensions show no significant short-term effects, implying that their benefits may emerge over a longer horizon through improved reputation and stakeholder confidence. The findings highlight the need for banks in Asia to prioritize governance reforms while progressively strengthening environmental and social initiatives to achieve balanced and sustainable growth. Future research is encouraged to expand the sample coverage, apply longer time horizons, and include broader performance indicators.